Linguistic philosophy : the central story - Hallett, Garth L., 1927-2022 (SUNY series in philosophy., 2008)
"How much authority should language, the medium of communication, be accorded as a determinant of truth and therefore of what we say? Garth L. Hallett argues that, although never explicitly debated, this is the most significant issue of linguistic philosophy. Here, for the first time, he traces the issue's story. Starting with representative thinkers - Plato, Aquinas, Kant, Frege, and the early Willgenstein - who contested language's authority, the narrative then focuses on thinkers such as Carnap, Tarski, the later Wittgenstein, Flew, Russell, Malcolm, Austin, Kripke, Putnam, Strawson, Quine, and Habermas who, in different ways and to varying degrees, accorded language more authority, implicit in this account is a challenge to philosophy as still widely practiced."--Jacket